Tensegrity laboratory drilling rig for earth and space drilling, mining, and exploration. (1st October 2022) - Khaled, Mohamed S.; Chen, Muhao; Losoya, Enrique Z.; Rodriguez, Luis A.; Gildin, Eduardo; Skelton, Robert E.
Abstract: Drilling operations are increasingly becoming a manufacturing process where repeatability, versatility, and speed matter the most for an operator or future space missions. Nonetheless, the ongoing energy transition efforts will undoubtedly shape the objectives and priorities of drilling operators into new markets with unexplored technical challenges. Versatility, mobility, and automated systems will play crucial roles in determining successful applications. This study explores and introduces the application of tensegrity-based structures, commonly used in space exploration, to Earth and Space drilling systems by modeling, designing, and building a tensegrity-based miniature drilling rig. Robust models for designing a drilling rig based on tensegrity structures and anticipated load conditions are presented. In addition, the drilling tests and experimental results described proving that the tensegrity could be applied to unusual applications such as drilling. The lightweight tensegrity-based structure is feasible for drilling applications on Earth and Mars by tuning design variables such as structure complexity, bar and string sizes, pre-stress, Etc. Tensegrity structures allow more volume-efficient, lightweight, and deployable mechanisms essential for space deployment. It also enhances rig mobility, reducing drilling costs and the environmental footprint of the Earth based-system by downsizing the site's carbon expenditure.